Horner syndrome as a complication of ultrasound-guided ablation therapy for thyroid nodules: a scoping review - Xie, Tianhao; Fu, Yan; Jin, Xiaoshi; Ren, Xiangxiang; Zhang, Jing; Sun, Qian (Frontiers in Endocrinology, 2025)
ObjectiveTo synthesize evidence on Horner syndrome (HS) as a complication of ultrasound-guided ablation therapy for thyroid nodules, including its incidence, mechanisms, risk factors, and prevention strategies, to enhance ablation safety and guide future research.Data sourcesWeb of Science, PubMed, Cochrane Library, and Embase.Review methodsBased on the framework of the PRISMA-ScR, a search was conducted in databases up to December 31, 2024.ResultsTwelve articles were included, covering Microwave Ablation (MWA), Radiofrequency Ablation (RFA), High-Intensity Focused Ultrasound (HIFU), and Percutaneous Ethanol Injection (PEI). HS incidence rates varied: MWA 0.4%-4.2%, RFA 0.1%-1.5%, HIFU 1.5%-6.7%, with PEI incidence unspecified due to insufficient data. HS mechanisms included thermal injury to the cervical sympathetic chain, nerve damage from ethanol extravasation, and mechanical compression. Risk factors included ablation zones adjacent to the middle cervical ganglion (MCG), improper ablation parameter settings (such as excessively high power or prolonged duration), and nodule locations near the inferior thyroid artery. Prevention strategies emphasized precise preoperative ultrasound localization of the CSC and MCG, optimization of the isolation belt technique, timely adjustment of ablation parameters, real-time monitoring of symptoms, and avoiding the ablation probe tip from extending beyond the nodule edge.ConclusionHS is a rare but serious complication with varying incidence rates by technique. Risk can be reduced through precise assessment, meticulous techniques, and technological innovations. Future prospective studies are needed to clarify incidence rates, long-term prognosis, and refine clinical practice guidelines.